Teach Yourself VISUALLY Complete Mac Pro. - McFedries, Paul (Teach Yourself VISUALLY (Tech), 2014)
Get up to speed on Apple's visionary new redesign of the desktop computer It has the sleek lines of a starship, all-Flash memory, rock-solid architecture, and connection ports galore. Now you can take a deep dive through all the killer new features and functions of Apple's visionary new Mac Pro desktop computer with our equally impressive new guide, Teach Yourself VISUALLY Complete Mac Pro. Clear screenshots and lessons show you how to tackle not only beginning but also intermediate and advanced functions. You'll soon be customizing your Mac Pro, creating digital media,